2016
DOI: 10.1111/vox.12394
|View full text |Cite
|
Sign up to set email alerts
|

The impact of donor characteristics on the immune cell composition of second allografts in Chinese people

Abstract: The results demonstrate the impact of the donor characteristics, including pre-FM platelet count and lymphocyte count, donor BMI and weight, on the immune cell composition in the second allograft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In haplo‐HCT with the Beijing protocol, Wang et al found that haplo‐HCT from young donors (< 30 years old) was associated with reduced NRM and better OS . This advantage may be related to the different cell populations (higher dose of CD34 + cells and CD3 + CD4 − CD8 − T cells in grafts from younger donors) . Moreover, in the TCD setting, donor age of less than 40 years was associated with faster immune reconstitution and decreased nonrelapse related mortality.…”
Section: Donor Agementioning
confidence: 99%
“…In haplo‐HCT with the Beijing protocol, Wang et al found that haplo‐HCT from young donors (< 30 years old) was associated with reduced NRM and better OS . This advantage may be related to the different cell populations (higher dose of CD34 + cells and CD3 + CD4 − CD8 − T cells in grafts from younger donors) . Moreover, in the TCD setting, donor age of less than 40 years was associated with faster immune reconstitution and decreased nonrelapse related mortality.…”
Section: Donor Agementioning
confidence: 99%